Magnetic and gravity source models of the Gairdner Dolerites. Issue 1 (1st December 2019) - Heath, Philip; Foss, Clive
Summary: The Gairdner Dolerites feature prominently in magnetic and gravity images of South Australia. They are a volcanic intrusive, easily identifiable in SA magnetic images as a set of NNW-SSE linear features. The Gawler Craton Airborne Survey (GCAS) has recently acquired high-resolution magnetic data over these dolerites. AutoMag analysis of magnetic data from the GCAS data is used to study the large number of Gairdner Dolerite dyke anomalies in the study area. A high-resolution (400 metre station spaced) gravity survey reveals that the larger dykes have detectable gravity expressions. We have inverted two selected dyke magnetic anomalies to derive source models with best-estimated thicknesses of 75 and 97 metres and magnetic susceptibilities of .054 and .029 respectively. These models together with density measurements of over 2, 900 kg/m3 for the dykes and less than 2, 600 kg/m 3 for Pandurra Formation which the dykes intrude are used to forward model gravity anomalies with peak amplitudes of 4 to 5 μm/sec 2 . We plan more detailed gravity traverses over selected dykes to test combined magnetic and gravity inversion with which to constrain depth to the top of basement (where there is a substantial reduction in density contrast).